2018
DOI: 10.1021/acsami.8b10445
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Device Efficiency and Long-Term Stability via Boronic Acid-Based Self-Assembled Monolayer Modification of Indium Tin Oxide in a Planar Perovskite Solar Cell

Abstract: Interfacial engineering is essential for the development of highly efficient and stable solar cells through minimizing energetic losses at interfaces. Self-assembled monolayers (SAMs) have been shown as a handle to tune the work function (WF) of indium tin oxide (ITO), improving photovoltaic cell performance and device stability. In this study, we utilize a new class of boronic acid-based fluorine-terminated SAMs to modify ITO surfaces in planar perovskite solar cells. The SAM treatment demonstrates an increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 42 publications
(69 reference statements)
2
27
0
Order By: Relevance
“…Interfacial modifications were carried out using a new series of fluorine‐functionalized boronic acid SAMs. 2F‐SAMs modification exhibits 16% efficiency and long‐term stability also provide a permanent ITO work function modification and prevents the degradation of ITO because of the acidic effect of PEDOT:PSS …”
Section: Structural Influence On the Stability Of Pscsmentioning
confidence: 99%
“…Interfacial modifications were carried out using a new series of fluorine‐functionalized boronic acid SAMs. 2F‐SAMs modification exhibits 16% efficiency and long‐term stability also provide a permanent ITO work function modification and prevents the degradation of ITO because of the acidic effect of PEDOT:PSS …”
Section: Structural Influence On the Stability Of Pscsmentioning
confidence: 99%
“…[ 150–153 ] Application of SAMs to PSCs have proved to be an excellent technique for not only improving the device efficiency but device stability as well. [ 107,121,143,145 ]…”
Section: Sams For Improving Perovskite Solar Cells Stabilitymentioning
confidence: 99%
“…More importantly, SAMs were introduced as new hole‐selective contacts and achieved a remarkable stabilized efficiency of 21.1%. Kara and co‐workers also modified the WF ITO with SAMs [ 143 ] by using boronic acid‐based fluorine‐terminated SAMs on top of the ITO. After 30 days in ambient conditions, the photovoltaic efficiency of the cells reduced by only 20%.…”
Section: Sams For Improving Perovskite Solar Cells Stabilitymentioning
confidence: 99%
“…Comprehensive efforts have been devoted to the investigation of all-inorganic lead halide perovskites with interesting and exciting potential applications, such as solar cells (SCs), lasers, light-emitting diodes, and photodetectors, owing to their superior electronic and photoelectric properties. However, the often used toxic heavy metals such as Pb still remain as the main block to hamper their future application. To date, it was reported that replacing Pb with homovalent nontoxic elements, such as Sb, Ba, Zn, Sn, Ge, Cu, and Mn, or heterovalent nontoxic elements in the form of double perovskite could effectively address the toxic issue. Lead-free perovskites need more efforts to explore their application in the photovoltaic field.…”
Section: Introductionmentioning
confidence: 99%